Mature cystic teratoma in a 12-year-old with situs inversus totalis: a case report in a Nigerian teaching hospital - Akinyoade, Richard Akindele; Ajenifuja, Kayode Olusegun; Adefuye, Peter Oladipupo; Akinyoade, Oluwatoyin Nike; Adebisi, Mathew Olumide; Gbala, Olumide Michael (International Journal of Research in Medical Sciences, 2025)
Mature cystic teratomas are the most common benign ovarian tumors in children, adolescents, usually composed of mature tissues from all three germ layers. Situs inversus totalis (SIT) is a rare congenital condition characterized by complete mirror-image reversal of thoracic and abdominal viscera. Coexistence of these two entities is extremely rare, with only a handful of cases reported worldwide. We describe a 12-year-old girl who presented to the University of Medical Sciences Teaching Hospital, Ondo, Nigeria, with progressive abdominal swelling of eight months’ duration, associated abdominal pain, weight loss, anorexia, and early satiety. Clinical and radiological evaluation revealed a huge heterogeneous ovarian mass with incidental findings of dextrocardia, left-sided liver and gallbladder, and right-sided spleen, consistent with SIT. She underwent exploratory laparotomy which demonstrated a lobulated left ovarian mass measuring 30×28 cm, moderate ascites, and complete visceral reversal. Left oophorectomy was performed. Histopathology confirmed a mature cystic teratoma. Her postoperative recovery was uneventful, and she remained well at follow-up. Mature cystic teratomas are common ovarian tumors in young females, but their association with SIT is exceptionally rare. The reversed anatomy poses diagnostic and surgical challenges, and careful preoperative evaluation is crucial. Complete excision remains the treatment of choice, with an excellent prognosis. This case appears to be the first documented report from Nigeria and contributes to the scarce global literature on this unusual association. This case highlights the importance of considering rare anatomic anomalies in surgical planning and underscores the need for thorough reporting of such cases in sub-Saharan Africa.